Comparison between inductively coupled plasma-mass spectrometry and benchtop X-ray fluorescence performance for trace elemental exposure in rat tissues - Kolawole E. Adesina; Stefano A. Parducci; Joseph D. Brain; Ramon M. Molina; Marc Weisskopf; Aaron J. Specht (Journal of Trace Elements and Minerals)
Background: Trace elemental toxicants induce health detriment in almost every organ system in the human body and account for a large amount of environmental and ecological environmental pollution. Traditionally, inductively coupled plasma mass spectrometry (ICP-MS) has been the gold standard for measuring elemental concentrations in biological tissues collected from toxicological and epidemiological studies. However, ICP-MS is often limited by its complexity, cost, and time-intensive nature. Methods: This study investigates the feasibility of benchtop X-ray fluorescence (XRF) as an efficient alternative for trace elemental analysis in rat tissues, offering comparable quantification capabilities with enhanced operational simplicity. We conducted a comparative analysis using tissue samples from multiple rat organs, including stomach, eyes, and liver. Results: The elemental concentrations of Arsenic (As), Cadmium (Cd), Copper (Cu), Manganese (Mn), and Zinc (Zn) were measured using both ICP-MS and a high-powered benchtop XRF (Epsilon 4, Malvern Panalytical). Our findings demonstrated strong linear regression correlations between the two methods: As (R² = 0.86), Cd (R² = 0.81), Cu (R² = 0.77), Mn (R² = 0.88), and Zn (R² = 0.74). The overall Pearson correlation coefficient was r = 0.95 (p ≤ 0.05), indicating high concordance between the mean concentrations obtained from ICP-MS and benchtop XRF. The median minimum detection limits for the elements were 0.12 µg/g, with specific limits for Cd (0.0042 µg/g), Cu (0.040 µg/g), Zn (0.12 µg/g), As (0.25 µg/g), and Mn (0.35 µg/g) over a 7.5-minute measurement period. Bland-Altman analysis revealed high agreement between the two methods, particularly for As, Cu, and Mn. Conclusion: These results suggest that both ICP-MS and benchtop XRF are viable for elemental quantification in organ tissues, with benchtop XRF being more practical for low-mass samples. This study shows benchtop XRF's potential for high-throughput, accurate trace element analysis in biological samples, broadening its use in environmental and toxicological research. Synopsis: Human and ecological tissues of varying compositions and densities can be measured effectively using benchtop X-ray fluorescence